Rapid detection of herpes simplex virus DNA by in situ hybridization with photobiotin-labelled double-stranded DNA probes - Wasun Chantratita (2018)
An assay for rapid detection of herpes simplex virus in infected cells is described. The assay utilizes in situ hybridization with photobiotin-labelled double-stranded DNA probes prepared from HSV-1 DNA cloned in plasmid vectors. The assay provided an alternative method for earlier detection of virus in cell cultures with the ease of preparation of photobiotin-labelled double-stranded DNA. © 1989.